Amphiphilic hyperbranched polyethyleneimine for highly efficient oil–water separation. Issue 5 (15th January 2020) - Yan, Shu; He, Guijin; Ye, Dengfeng; Guo, Yongsheng; Fang, Wenjun
Abstract : Core–shell structural amphiphilic soft matter, HPEI- g -C n, can achieve phase separation thoroughly, in which an interfacial active-polymer layer is formed after demulsification. Abstract : To deal with the demulsification of O/W emulsions, a novel kind of core–shell structural amphiphilic soft matter, HPEI- g -C n ( n = 10, 12, 14, 16, 18), with hyperbranched polyethyleneimine (HPEI) as the core and fatty acid chain C n as the shell, is designed and synthesized. With the existence of amphiphilic HPEI- g -C n, O/W emulsions can be thoroughly separated into two phases with a clear oil–water interface to reach demulsification equilibrium within 40 min. The oil removal ratio can exceed 99.9% under the addition of 40 ppm in simulative emulsions, and simultaneously the water content in the oil phase is less than 0.01%. This demulsifier can also contribute to excellent separation efficiency (up to 99.9%) for O/W emulsions from two China's oilfields, and even for heavy oil emulsions. More importantly, it is noted that the HPEI- g -C n demulsifiers after demulsification are evenly and tightly dispersed at the oil–water interface as shown by wide-angle X-ray scattering (WAXS) and cryo-electron microscopy (cryo-EM), which is beneficial to the subsequent recovery and utilization. With eco-friendly characteristics, outstanding demulsification performance and promising recyclability, the amphiphilic macromolecules HPEI- g -C n as special soft matter display great promise to achieve industrial applications in the future.